Oxidation halide solid electrolyte composite material, preparation method thereof and battery
By designing the core-shell structure on the solid electrolyte composite of oxyhalide and preparing it through the gas phase surface fluorination method, the problem of reduced conductivity caused by fluorine doping is solved, and the high oxidation potential and air stability are improved, and the The energy density and positive electrode capacity of the battery are obtained.
Patent Information
- Application Number
- CN202411385870.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
AI Technical Summary
Fluorine-doped oxyhalide electrolytes lead to a significant reduction in the ionic conductivity of the material electrolyte, which makes it difficult to meet the requirements of high oxidation potential and air stability.
An oxyhalide solid electrolyte composite material with a core-shell structure is used, and the surface shell part of its surface shell is a fluorine-containing component LiaMObClc-dFd, and the inner core part is a fluorine-free component LiaMObClc. It is prepared by the gas phase surface fluorination method.
While maintaining high ionic conductivity, the electrochemical oxidation potential and air stability are improved, and the capacity of the positive electrode active material and the energy density of the battery are enhanced.
Smart Images

Figure BDA0005070971050000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a halogen oxide solid electrolyte composite material, a preparation method thereof, and a battery. Background Art
[0002] Since traditional lithium-ion batteries need to use flammable organic solvents as electrolytes, there are great safety risks. In comparison, solid-state lithium-ion batteries using solid electrolytes have greater safety advantages. The use of solid electrolytes can not only fundamentally solve the safety problems of lithium-ion batteries, but also greatly simplify the manufacturing and packaging process, and improve the energy density, reliability and design freedom of the battery.
[0003] In order to meet the demand for high energy density, the positive electrode material is usually matched with the high-potential ternary positive electrode material, so a strong requirement is put forward for the high potential stability of the electrolyte (>4V). Among inorganic electrolyte materials, oxide electrolytes have high oxidation potentials and are stable to high-voltage ternary positive electrode materials; however, oxide electrolyte materials are difficult to achieve high ionic conductivity, and have high rigidity and poor ductility, resulting in a large contact impedance with the positive electrode material. In comparison, sulfide electrolyte systems usually have high ionic conductivity, good ductility, and can form a relatively dense physical contact with the positive electrode material; however, the raw material cost of sulfide electrolytes is relatively high, the oxidation potential is low (usually <3V), and when it is in direct contact with the positive electrode material, serious side reactions will occur during the cycle. In addition, oxyhalide solid electrolytes are a type of solid electrolyte material that has recently received attention. They have many advantages such as high ionic conductivity, good ductility, and stability to the positive electrode. For example, the ionic conductivity of LiNbOCl4 reported in the literature (Angew.Chem.Int.Ed.2023,62,e202217581.) can reach 10.7mS / cm, and it can be cycled at a higher voltage (~4.2V) when mixed with ternary active materials as a positive electrode layer. However, in order to make the positive electrode material have a higher capacity, it is difficult for oxyhalide electrolytes to meet the requirements of higher oxidation potentials (>4.5V). In addition, such materials have the disadvantages of being extremely easy to absorb moisture and having poor air stability. Fluorine doping of halide electrolytes is an effective means to improve their voltage window and air stability, but because the ionic conductivity of fluorides is very low, fluorine doping usually leads to a significant reduction in the ionic conductivity of the material electrolyte. Summary of the invention
[0004] In view of this, the present invention is committed to providing a halide oxide solid electrolyte composite material and a preparation method and a battery thereof, so as to solve the problem in the prior art that fluorine-doped halide oxide electrolytes cause a significant decrease in the ionic conductivity of the material electrolyte.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] The first aspect of the present invention provides a halogen oxide solid electrolyte composite material, which includes core particles and a coating layer coated on the surface of the core particles;
[0007] The core particles include Li a MO b X c , and the coating layer material includes Li a MO b X c-d F d , where 0.1 ≤ a ≤ 5, 0 < b ≤ 2, 2 ≤ c ≤ 6, 0 < d ≤ 2; M is selected from at least one of Hf, Zr, Nb, Ta, and Ti, and X is selected from at least one of Cl, Br, and I.
[0008] Optionally, the core particles include Li a MO b X c , and the coating layer material includes Li a MO b X c-d F d , where 0.8 ≤ a ≤ 3.5, 0.2 ≤ b ≤ 1.5, 3.5 ≤ c ≤ 5.8, 0.1 ≤ d ≤ 1.
[0009] Optionally, the M is selected from at least one of Hf, Zr, Nb, and Ta; the X is selected from Cl and / or Br; preferably, the M is selected from Nb and / or Ta.
[0010] Optionally, the D50 of the halogen oxide solid electrolyte composite material is 0.05 - 100 μm, preferably 0.2 - 20 μm; the thickness of the coating layer is 1 - 100 nm.
[0011] The second aspect of the present invention provides a method for preparing a halogen oxide solid electrolyte composite material, and the preparation method includes the following steps:
[0012] S1. Mix lithium halide and the halogen oxide of M and then perform ball milling treatment to obtain a first material;
[0013] S2. Sinter the first material in an inert atmosphere to obtain a second material;
[0014] S3. Perform fluorination treatment on the second material;
[0015] where M is selected from at least one of Hf, Zr, Nb, Ta, and Ti, and the lithium halide is selected from at least one of LiCl, LiBr, and LiI.
[0016] Optionally, the molar ratio of the lithium halide and the halide oxide of M is 1:0.3-1.
[0017] Optionally, in step S1, the conditions of the ball milling treatment include: a rotation speed of 300 to 800 rpm and a time of 1 to 25 hours.
[0018] Optionally, in step S2, the inert atmosphere includes argon and / or nitrogen; the sintering treatment conditions include: a temperature of 100 to 240° C. and a time of 1 to 40 hours.
[0019] Optionally, in step S3, the fluorination treatment includes heat treating the second material in a fluorine-containing atmosphere; the fluorine-containing atmosphere includes fluorine gas and / or HF; the conditions of the heat treatment include: a temperature of 100 to 220° C. and a time of 0.1 to 100 min.
[0020] A third aspect of the present invention provides a battery, which includes an electrolyte material, wherein the electrolyte material includes the above-mentioned oxyhalide solid electrolyte composite material and / or the oxyhalide solid electrolyte composite material prepared according to the above-mentioned preparation method.
[0021] Through the above technical solution, the beneficial technical effects of the present invention are:
[0022] (1) The present invention provides a halogen oxide solid electrolyte composite material having a core-shell structure, wherein the surface shell portion is a fluorine-containing component Li a MO b Cl c-d F d , the core part of which is the fluorine-free component Li a MO b Cl c , the F element is only distributed on the surface of the solid electrolyte material powder particles, which makes the main body of the material contain low fluorine content, reduces the negative impact of low conductivity caused by the high fluorine content of the material as a whole, and promotes the oxyhalide solid electrolyte composite material to have excellent electrochemical oxidation potential and air stability while maintaining high ionic conductivity. Therefore, the oxyhalide solid electrolyte composite material of the present invention has excellent comprehensive performance, which helps to improve the capacity of the positive electrode active material and the energy density of the battery, thereby realizing the commercial application value of the all-solid-state secondary battery.
[0023] (2) The preparation method of the oxyhalide solid electrolyte composite material of the present invention uses a vapor phase surface fluorination method to fluorinate the surface of the electrolyte material under relatively mild synthesis conditions. The reaction conditions of the method of the present invention are relatively mild, and the use of high-energy ball milling can be avoided, thereby simplifying the process flow, facilitating large-scale preparation, and being suitable for industrial production.
[0024] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0025] The present invention discloses a halogen oxide solid electrolyte composite material and a preparation method and battery thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0026] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0027] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0030] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0031] To solve the problem that the fluorine-doped oxyhalide electrolyte in the prior art causes a significant reduction in the ionic conductivity of the material electrolyte, the present invention adopts the following technical solutions:
[0032] In a first aspect of the present invention, there is provided an oxyhalide solid electrolyte composite material, which includes core particles and a coating layer coated on the surface of the core particles;
[0033] The core particles include Li a MO b X c , and the coating layer material includes Li a MO b X c-d F d , where 0.1 ≤ a ≤ 5, 0 < b ≤ 2, 2 ≤ c ≤ 6, 0 < d ≤ 2; M is selected from at least one of Hf, Zr, Nb, Ta, and Ti, and X is selected from at least one of Cl, Br, and I.
[0034] The oxyhalide solid electrolyte composite material of the present invention has a core-shell structure. By coating a fluorine-containing electrolyte layer on the surface of the high ionic conductivity oxyhalide, it is possible to improve the voltage window and air stability of the electrolyte material while maintaining high ionic conductivity and good mechanical strength. When the oxyhalide solid electrolyte composite material of the present invention is matched with a high-voltage cathode material, the battery can have excellent cycle performance and rate performance.
[0035] According to the present invention, the core particles may include Li a MO b X c , and the coating layer material may include Li a MO b X c- d F d , where 0.8 ≤ a ≤ 3.5, 0.2 ≤ b ≤ 1.5, 3.5 ≤ c ≤ 5.8, 0.1 ≤ d ≤ 1.
[0036] According to the present invention, the M may be selected from at least one of Hf, Zr, Nb, and Ta; the X may be selected from Cl and / or Br. As a preferred embodiment of the present invention, the M may be selected from Nb and / or Ta.
[0037] According to the present invention, the D50 of the oxyhalide solid electrolyte composite material can be 0.05 to 100 μm. Exemplarily, the D50 of the oxyhalide solid electrolyte composite material can be any value among 0.05 μm, 0.1 μm, 1 μm, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm and 10 μm, or any value within the range of any two of the above values. In the present invention, if the D50 of the oxyhalide solid electrolyte composite material is too small, the ionic conductivity will be low. If the D50 of the oxyhalide solid electrolyte composite material is too large, the contact with the positive and negative electrodes will be poor. Preferably, the D50 of the oxyhalide solid electrolyte composite material is 0.2 to 20 μm.
[0038] In the present invention, a suitable coating layer thickness is conducive to improving air stability while maintaining high ionic conductivity. If the coating layer thickness is too low, the air stability will be poor. If the coating layer thickness is too high, the ionic conductivity loss will be large. According to the present invention, the thickness of the coating layer can be 1 to 100 nm. Exemplarily, the thickness of the coating layer can be any value among 1 nm, 10 nm, 20 nm, 40 nm, 60 nm, 80 nm and 100 nm, or any value within the range of any two of the above values.
[0039] A second aspect of the present invention provides a method for preparing an oxyhalide solid electrolyte composite material, the preparation method comprising the following steps:
[0040] S1, mixing lithium halide and the halide oxide of M and subjecting the mixture to ball milling to obtain a first material;
[0041] S2, sintering the first material in an inert atmosphere to obtain a second material;
[0042] S3, fluorinating the second material;
[0043] Wherein, M is selected from at least one of Hf, Zr, Nb, Ta and Ti, and the lithium halide is selected from at least one of LiCl, LiBr and LiI.
[0044] The preparation method of the present invention performs gas phase surface fluorination on the oxyhalide solid electrolyte, and realizes the surface fluorination of the oxyhalide solid electrolyte through gas-solid reaction to form an oxyhalide solid electrolyte composite material with a core-shell structure. The reaction conditions of the method of the present invention are relatively mild, and the use of high-energy ball milling can be avoided, the process flow is simplified, and it is easy to prepare in large quantities, which is suitable for industrial production. The surface shell layer of the oxyhalide solid electrolyte composite material prepared by the present invention is a fluorine-containing component Li a MO b X c-d F d, the core part of which is the fluorine-free component Li a MO b X c The halogen oxide solid electrolyte composite material prepared by the method of the present invention has a lower main fluorine content, so that the solid electrolyte material can maintain high ion conductivity and good mechanical strength while improving the material voltage window and air stability.
[0045] According to the present invention, the molar ratio of the lithium halide and the halide oxide of M can be 1:0.3-1.
[0046] According to the present invention, in step S1, the conditions of the ball milling treatment may include: a rotation speed of 300 to 800 rpm and a time of 1 to 25 hours.
[0047] According to the present invention, in step S2, the inert atmosphere may include argon and / or nitrogen; the sintering treatment conditions may include: a temperature of 100 to 240°C and a time of 1 to 40 hours. Preferably, the sintering treatment time is 5 to 30 hours.
[0048] According to the present invention, in step S3, the fluorination treatment may include heat treating the second material in a fluorine-containing atmosphere; the fluorine-containing atmosphere may include fluorine gas and / or HF; the heat treatment conditions may include: a temperature of 100 to 220°C and a time of 0.1 to 100 min. Preferably, the heat treatment time is 1 to 10 min.
[0049] A third aspect of the present invention provides a battery, which includes an electrolyte material, wherein the electrolyte material includes the above-mentioned oxyhalide solid electrolyte composite material and / or the oxyhalide solid electrolyte composite material prepared according to the above-mentioned preparation method.
[0050] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0051] Example 1
[0052] (1) LiCl and NbOCl3 are weighed in a molar ratio of 1:1, added into a sealed ball mill, and ball milled at 550 rpm for 20 h using a planetary ball mill to obtain a first material.
[0053] (2) The first material is sintered in an argon atmosphere at a sintering temperature of 120° C. for a sintering time of 2 h to obtain a second material having a composition of LiNbOCl4.
[0054] (3) Under normal temperature and pressure, the second material is subjected to fluorination treatment, wherein the fluorination treatment comprises: heat treatment in a dry HF atmosphere at a temperature of 120° C. for a time of 6 min to obtain a halogen oxide solid electrolyte composite material.
[0055] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.2 μm, and the F element is distributed in an area with a depth of ≤60 nm on the surface of the powder particles.
[0056] Example 2
[0057] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in Embodiment 1, except that the fluorination treatment in this embodiment includes heat treatment in a dry HF atmosphere at a temperature of 120° C. for a time of 1 min.
[0058] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.4 μm, and the F element is distributed in an area with a depth of ≤15 nm on the surface of the powder particles.
[0059] Example 3
[0060] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in Embodiment 1, except that the fluorination treatment in this embodiment includes heat treatment in a dry HF atmosphere at a temperature of 120° C. for 3 minutes.
[0061] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 6.8 μm, and the F element is distributed in an area with a depth of ≤58 nm on the surface of the powder particles.
[0062] Example 4
[0063] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in Embodiment 1, except that the fluorination treatment in this embodiment includes heat treatment in a dry HF atmosphere at a temperature of 120° C. for 10 min.
[0064] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.5 μm, and the F element is distributed in an area with a depth of ≤95 nm on the surface of the powder particles.
[0065] Example 5
[0066] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiCl and NbO 0.8 Cl 3.4 The molar ratio of is 1.1:1, and the second material prepared in step (2) is Li 1.1 NbO 0.8 Cl 4.5 .
[0067] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.8 μm, and the F element is distributed in an area with a depth of ≤58 nm on the surface of the powder particles.
[0068] Example 6
[0069] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in embodiment 1, except that: in this embodiment, LiCl and NbO 1.5 The molar ratio of Cl2 is 1.5:1, and the second material prepared in step (2) is Li 1.5 NbO 1.5 Cl 3.5 .
[0070] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 8.1 μm, and the F element is distributed in an area with a depth of ≤59 nm on the surface of the powder particles.
[0071] Example 7
[0072] The preparation method of the halogen oxide solid electrolyte composite material in this embodiment is the same as that in Example 1, except that the raw materials in step (1) of this embodiment are LiCl and TaOCl3, the molar ratio of LiCl and TaOCl3 is 1:1, and the second material prepared in step (2) is LiTaOCl4.
[0073] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.5 μm, and the F element is distributed in an area with a depth of ≤62 nm on the surface of the powder particles.
[0074] Example 8
[0075] The preparation method of the halogen oxide solid electrolyte composite material in this embodiment is the same as that in Example 1, except that the raw materials in step (1) of this embodiment are LiCl and HfOCl2, the molar ratio of LiCl to HfOCl2 is 3:1, and the second material prepared in step (2) is Li3HfOCl5.
[0076] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 8.4 μm, and the F element is distributed in an area with a depth of ≤57 nm on the surface of the powder particles.
[0077] Example 9
[0078] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in embodiment 1, except that the raw materials in step (1) of this embodiment are LiCl and ZrO 0.2 Cl 3.6 , LiCl and ZrO 0.2 Cl 3.6 The molar ratio of Li is 2.2:1, and the second material prepared in step (2) is Li 2.2 ZrO 0.2 Cl 5.8 .
[0079] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.4 μm, and the F element is distributed in an area with a depth of ≤62 nm on the surface of the powder particles.
[0080] Example 10
[0081] The preparation method of the halogen oxide solid electrolyte composite material in this embodiment is the same as that in embodiment 1, except that: the raw materials in step (1) of this embodiment are LiCl and ZrOCl3, the molar ratio of LiCl to ZrOCl3 is 1:0.4, and the second material prepared in step (2) is Li 2.5 ZrO 0.5 Cl 5.5 .
[0082] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.2 μm, and the F element is distributed in an area with a depth of ≤63 nm on the surface of the powder particles.
[0083] Embodiment 11
[0084] The preparation method of the oxyhalide solid electrolyte composite material of this embodiment is the same as that of embodiment 1, except that: the raw materials in step (1) of this embodiment are LiBr, LiCl and NbOBr3, the molar ratio of LiBr, LiCl and NbOBr3 is 1:1:2, and the second material prepared in step (2) is LiNbOCl 3.5 Br 0.5 .
[0085] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 7.3 μm, and the F element is distributed in an area with a depth of ≤62 nm on the surface of the powder particles.
[0086] Example 12
[0087] The preparation method of the oxyhalide solid electrolyte composite material in this embodiment is the same as that in Example 1, except that the raw materials in step (1) of this embodiment are LiCl, LiBr and ZrO 0.5 Cl3, LiCl, LiBr and ZrO 0.5 The molar ratio of Cl3 is 1.7:0.8:1, and the second material prepared in step (2) is Li 2.5 ZrO 0.5 Cl 4.7 Br 0.8 .
[0088] By performing dry particle size measurement on the oxyhalide solid electrolyte composite material in this embodiment, it is measured that the D50 of the oxyhalide solid electrolyte composite material is 6.8 μm, and the F element is distributed in an area with a depth of ≤57 nm on the surface of the powder particles.
[0089] Comparative Example 1
[0090] (1) LiCl and NbOCl3 are weighed in a molar ratio of 1:1, added into a sealed ball mill, and ball milled at 550 rpm for 20 h using a planetary ball mill to obtain a first material.
[0091] (2) The first material is sintered in an argon atmosphere at a sintering temperature of 120° C. for a sintering time of 2 h to obtain a halide oxide electrolyte material having a composition of LiNbOCl4.
[0092] Comparative Example 2
[0093] (1) LiCl, LiF and NbOCl3 are weighed according to a molar ratio of 0.5:0.5:1, added into a sealed ball mill, and ball milled at 550 rpm for 20 h using a planetary ball mill to obtain a first material.
[0094] (2) The first material was sintered in an argon atmosphere at a temperature of 120° C. for a sintering time of 2 h to obtain a halide oxide electrolyte material having a composition of LiNbOCl 3.5 F 0.5 .
[0095] Comparative Example 3
[0096] (1) LiCl, LiF, Li2O and ZrCl4 were weighed according to a molar ratio of 1.3:0.5:0.2:1, added into a sealed ball mill, and ball milled for 20 h at a rotation speed of 550 rpm using a planetary ball mill to obtain a first material.
[0097] (2) The first material was sintered in an argon atmosphere at a temperature of 120° C. for 2 h to obtain a halide oxide electrolyte material having a composition of Li 2.2 ZrO 0.2 Cl 5.3 F 0.5 .
[0098] Test Example 1
[0099] The electrolyte materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were subjected to ion conductivity test before exposure, ion conductivity test after exposure and electrochemical oxidation potential test. The test results are shown in Table 1.
[0100] The ionic conductivity test method includes: weighing 100 mg of electrolyte powder, placing it inside a mold for pressurization, applying a pressure of 300 MPa to the electrolyte powder for pressurization, and using an electrochemical workstation (Solarton1260) and an electrochemical impedance measurement method to measure the impedance value of the electrolyte material at room temperature (25°C) under the applied pressure. The real value of the impedance at the measurement point where the absolute value of the phase of multiple impedances is the smallest is used as the resistance value RSE of the electrolyte material relative to ion transfer. Using this resistance value, the ionic conductivity is calculated based on the formula σ=(RSE×S / t)-1. Among them, σ is the ionic conductivity, RSE is the resistance value of the measured electrolyte material, S is the surface area of the electrolyte material to which pressure is applied, and t is the thickness of the electrolyte material to which pressure is applied.
[0101] The test method for ionic conductivity after dry room exposure includes: taking a sample after the above-mentioned ionic conductivity test, the room temperature ionic conductivity is recorded as σ0, taking a 2g sample, placing it in a -45℃ dew point environment for 24 hours, and measuring the room temperature ionic conductivity after placement. The test method is the same as above, and the ionic conductivity after the test is σ t .
[0102] The electrochemical oxidation potential test method includes: measuring the electrochemical oxidation stability potential using linear voltammetry, the battery configuration is BE / SSE+C / SSE / Li, the scan rate is 1mV / s, and the voltage range is Voc~7V.
[0103] Table 1
[0104]
[0105] It can be seen from Table 1 that the ionic conductivity and voltage window of the oxyhalide solid electrolyte composite material prepared in this embodiment are significantly improved after exposure. Therefore, the oxyhalide solid electrolyte composite material of the present invention can improve the voltage window of the material while maintaining high ionic conductivity.
[0106] Test Example 2
[0107] The electrolyte materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 were subjected to solid-state battery cycle performance tests. The test results are shown in Table 2.
[0108] The solid-state battery cycle performance test includes: under an argon atmosphere, weighing the solid electrolyte and NCM811 positive electrode in a ratio of 25:75, and evenly mixing to obtain a composite positive electrode material. In an insulating test sleeve with a diameter of 10 mm, add 100 mg of Li6PS5Cl sulfide solid electrolyte, apply a pressure of 300 MPa and hold the pressure for 2 minutes, and the solid electrolyte layer is formed. Pour 20 mg of the obtained composite positive electrode material into the first side of the pressed electrolyte layer, apply a pressure of 360 MPa and hold the pressure for 5 minutes to form. Load the lithium-indium alloy sheet into the other side of the electrolyte layer and apply a pressure of 80 MPa to form. The positive electrode composite layer, solid electrolyte layer, lithium-indium alloy sheet and stainless steel current collectors on both sides constitute a test all-solid-state battery. The assembled all-solid-state battery pack is placed in a 25°C constant temperature box to test the battery cycle performance. The test conditions are to use a current density of 1C to test the first week charge and discharge performance and cycle charge and discharge performance of the solid-state battery. The voltage range is set to 2.7-4.5V (Li+ / Li) during the test process.
[0109] Among them, the first week charge and discharge performance test includes: solid-state battery constant current charge and discharge test, 1C rate, voltage range of 2.7 ~ 4.5V. The specific operation is: constant current charging to 4.5V at a current density of 1C, and the charge capacity at this time is recorded as the first charge capacity; constant current discharge at a current density of 1C, from 4.5V to a cut-off voltage of 2.7V, and the discharge capacity at this time is recorded as the first discharge capacity.
[0110] The 100-week capacity retention rate is: 100-week discharge specific capacity / first-week discharge specific capacity*100%.
[0111] Table 2
[0112] Example <![CDATA[Initial - week discharge specific capacity / mAh g -1 > 100-week capacity retention rate / % Example 1 225 93.2 Example 2 226 91.8 Example 3 222 94.3 Example 4 218 97.2 Example 5 220 95.9 Example 6 222 96.3 Example 7 228 95.7 Example 8 215 96.0 Example 9 211 94.8 Example 10 214 95.3 Embodiment 11 219 93.7 Example 12 217 92.4 Comparative Example 1 198 65.8 Comparative Example 2 204 87.2 Comparative Example 3 201 88.1
[0113] It can be seen from Table 2 that the battery prepared by matching the oxyhalide solid electrolyte composite material prepared in this embodiment with a high-voltage positive electrode material exhibits excellent cycle performance and rate performance.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A halide oxide solid electrolyte composite material, characterized in that: The oxyhalide solid electrolyte composite material comprises a core particle and a coating layer coated on the surface of the core particle; Among them, the core particles include Li a MO b X c , and the coating material includes Li a MO b X c-d F d , where 0.1 ≤ a ≤ 5, 0 < b ≤ 2, 2 ≤ c ≤ 6, 0 < d ≤ 2; M is selected from at least one of Hf, Zr, Nb, Ta, and Ti, and X is selected from at least one of Cl, Br, and I.
2. The oxyhalide solid electrolyte composite material according to claim 1, characterized in that: The core particles include Li a MO b X c , the coating layer material includes Li a MO b X c-d F d , among which, 0.8≤a≤3.5, 0.2≤b≤1.5, 3.5≤c≤5.8, 0.1≤d≤1.
3. The oxyhalide solid electrolyte composite material according to claim 1, characterized in that: The M is selected from at least one of Hf, Zr, Nb and Ta; the X is selected from Cl and / or Br; Preferably, the M is selected from Nb and / or Ta.
4. The oxyhalide solid electrolyte composite material according to claim 1, characterized in that: The D50 of the oxyhalide solid electrolyte composite material is 0.05 to 100 μm, preferably 0.2 to 20 μm; The coating layer has a thickness of 1 to 100 nm.
5. A method for preparing the oxyhalide solid electrolyte composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1, mixing lithium halide and the halide oxide of M and subjecting the mixture to ball milling to obtain a first material; S2, sintering the first material in an inert atmosphere to obtain a second material; S3, fluorinating the second material; Wherein, M is selected from at least one of Hf, Zr, Nb, Ta and Ti, and the lithium halide is selected from at least one of LiCl, LiBr and LiI.
6. The preparation method according to claim 5, characterized in that: The molar ratio of the lithium halide and the halide oxide of M is 1:0.3-1.
7. The preparation method according to claim 5, characterized in that: In step S1, the conditions of the ball milling treatment include: a rotation speed of 300 to 800 rpm and a time of 1 to 25 hours.
8. The preparation method according to claim 5, characterized in that: In step S2, the inert atmosphere includes argon and / or nitrogen; the sintering treatment conditions include: temperature of 100 to 240°C and time of 1 to 40 hours.
9. The preparation method according to claim 5, characterized in that: In step S3, the fluorination treatment includes heat treating the second material in a fluorine-containing atmosphere; The fluorine-containing atmosphere includes fluorine gas and / or HF; The heat treatment conditions include: temperature of 100 to 220° C. and time of 0.1 to 100 min.
10. A battery, characterized in that: The battery comprises an electrolyte material, wherein the electrolyte material comprises the oxyhalide solid electrolyte composite material according to any one of claims 1 to 4 and / or the oxyhalide solid electrolyte composite material prepared according to the preparation method according to any one of claims 5 to 9.
Citation Information
Cited By
Solid-state electrolyte, preparation method thereof and solid-state lithium battery
CN119852509A
Preparation method and application of solid electrolyte membrane
CN119920957A
Halide electrolyte, positive plate and solid-state battery
CN121812710A
Halide electrolyte, positive electrode sheet, and solid-state battery
CN121812710B